Sugar and spite [large type] - Beaton, M. C.; Green, R. W. (Novelist) (Beaton, M. C. Agatha Raisin mystery, 2025)
"When a series of deaths within the small Cotswolds birdwatching community begins to unravel her village, Agatha and her team at Raisin Investigators are certain there has been foul play involved. Now,they must dig up decades' worth of tempestuous relationships and simmering secrets among the birdwatching enthusiasts of the village inorder to prevent any further deaths. But with Agatha's own relationship with John Glass on the rocks after he is called away on his jobas a cruise ship dance instructor, and Sir Charles Fraith now attempting to step into John's shoes as her lover, Agatha has her work cut out her"--